2022
DOI: 10.3390/ijms23158653
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA in Acromegaly: Involvement in the Pathogenesis and in the Response to First-Generation Somatostatin Receptor Ligands

Abstract: Acromegaly is a chronic and systemic disease due to excessive growth hormone and insulin-like growth factor type I caused, in the vast majority of cases, by a GH-secreting pituitary adenoma. About 40% of these tumors have somatic mutations in the stimulatory G protein alpha-subunit 1 gene. The pathogenesis of the remaining tumors, however, is still not fully comprehended. Surgery is the first-line therapy for these tumors, and first-generation somatostatin receptor ligands (fg-SRL) are the most prescribed medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 99 publications
0
15
0
Order By: Relevance
“…Therefore, circulating miRNAs were considered biomarkers of disease due to their ability to regulate gene expression in distal cells or organs. 15,18,19…”
Section: Micrornasmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, circulating miRNAs were considered biomarkers of disease due to their ability to regulate gene expression in distal cells or organs. 15,18,19…”
Section: Micrornasmentioning
confidence: 99%
“…15−17 Circulating miRNAs were usually transported by apoptotic bodies, extracellular vesicles, and exosomes. 15,87 The previous study reported that exosome miRNA was involved in intercellular communication during carcinogenesis induced by arsenic exposure. 136 Exosome miR-21 secreted from arsenictransformed HBE cells can be transferred into normal HBE cells and regulated many biological events in the recipient cells.…”
Section: Dysregulation Of Mirnas In Arsenic-induced Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, many GH-secreting pituitary adenomas harbor chromosomal alterations such as somatic copy number alterations at extensive sites across the genomes. However, epigenetic mechanisms also appear to play a very important role, and Henriques et al dedicate an excellent review to current knowledge regarding microRNAs (miRNAs) in acromegaly, addressing their mechanisms of action, their potential role as biomarkers in pathological processes, specific miRNAs associated with acromegaly tumorigenesis as well as resistance to first-generation somatostatin analogs [ 7 ]. Several differentially expressed miRNAs are associated with proliferation, invasion, size, and even tumor suppression.…”
mentioning
confidence: 99%